Keterampilan Dasar Mengajar “Mengasah Keterampilan Dasar Mengajar: Fondasi Menjadi Guru Profesional” - Cut Kumala Sari; Kinanti Kinanti; Salwa Nazira (Lembaga Pengembangan Kinerja Dosen, 2025)
The teaching profession holds a pivotal role in shaping future generations. A teacher's effectiveness is determined not only by subject matter expertise but also by a set of fundamental teaching skills that form the bedrock of professional practice. This article aims to investigate and explore the essential basic teaching competencies required for educators to perform their duties effectively. Through a review of relevant literature and a synthesis of various sources, this paper identifies core skills such as lesson opening and closure techniques, material explanation abilities, questioning strategies, reinforcement provision, variation implementation, classroom management proficiency, and small group discussion facilitation. It is argued that the mastery and effective application of these foundational skills are crucial for creating quality learning experiences and significantly contribute to the optimal development of students' potential.